Using MOORA Method for Finding Best Dressing Parameters for Surface Grinding Hardox 500 - Binh, Vu Duc; Trang, Nguyen Van; Huong, Truong Thi Thu (European Journal of Applied Sciences, 2024)
This study reports the findings on the use of the multi-criteria decision-making (MCDM) method to determine the optimal dressing mode for surface grinding of Hardox 500. The research examined the MCDM issue utilizing the Multi-Objective Optimization based on Ratio Analysis (MOORA) method, with criterion weights determined through the Entropy method. Furthermore, surface roughness (RS) and material removal rate (MRR) were identified as the two criteria for this study. Additionally, five dressing variables were investigated: non-feeding dressing nn, fine dressing depth df, fine dressing times nf, rough dressing depth dr, and rough dressing times nr. Additionally, 16 experimental runs were designed and conducted using the L16 (44 x 21) design type. The issue related to MCDM has been assessed. The investigation's findings indicate that option No. 5, defined by the input parameters dr = 0.02 (mm), nr = 1, nf = 1, df = 0.01 (mm), and nn = 2, represents the optimal dressing mode.